Characterizing Spectral Channels of Visible Emission Line Coronagraph of Aditya-L1 - Patel, Ritesh; Megha, A.; Shrivastav, Arpit Kumar; Pant, Vaibhav; Vishnu, M.; Sankarasubramanian, K.; Banerjee, Dipankar (Frontiers in Astronomy and Space Sciences, 2021)
Aditya-L1 is India’s first solar mission with Visible Emission Line Coronagraph (VELC) consisting of three spectral channels taking high-resolution spectroscopic observations of the inner corona up to 1.5 R$_\odot$ at 5303 Å, 7892 Å, and 10747 Å. In this work, we present the strategy for the slit-width optimization for the VELC using synthetic line profiles by taking into account the instrument characteristics and coronal conditions for log(T) varying from 6 to 6.5. The synthetic profiles are convolved with simulated instrumental scattered light and noise to estimate the signal-to-noise ratio (SNR), which will be crucial to design the future observation plans. We find that the optimum slit width for VELC turns out to be 50 $μ$m providing sufficient SNR for observations in different solar conditions. We also analyzed the effect of plasma temperature on the SNR at different heights in the VELC field-of-view for the optimized slit-width. We also studied the expected effect of the presence of a CME on the spectral channel observations. This analysis will help to plan the science observations of VELC in different solar conditions.